PENGARUH COST OF GOODS SOLD DAN BIAYA ADMINISTRASI & UMUM TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR BEI - Irene Hari Anakia Situmorang; Lorina Siregar Sudjiman (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to investigate the impact of Cost of Goods Sold (COGS) and administrative costs on profitability in the consumer cyclicals sector during the 2019-2022 period. The method applied is a quantitative research method with a descriptive approach, sourcing secondary data on company financial statements through purposive sampling method. The analysis results show that overall, both Cost of Goods Sold and Administrative Costs have a significant impact on Profitability, with a Coefficient of Determination of 48.4%. The remaining 51.6% is attributed to other variables not examined in this study that also affect profitability. Partially, both variables, namely Cost of Goods Sold and Administrative and General Expenses, have a significant influence on Profitability.